PWE-052 Why Colonoscopy does not Prevent Right Sided Colorectal Cancer?. (4th June 2013) - Krupa, L; Tighe, R; Phillips, G
Abstract : Introduction: Colonoscopy is widely used for colorectal cancer screening and prevention. There is good evidence that it is associated with lower CRC mortality due to fewer deaths from left-sided cancers. Unfortunately it seems to be less effective in preventing right-sided colorectal cancers (1.2). There are several plausible causes for this finding. One of the reasons could be that right sided lesions are more difficult to detect due to different morphological characteristics. Methods: The adenoma detection rates (ADR) across the East of England within the Bowel cancer screening programme are monitored as part of the QA process. 30 colonoscopists across 8 screening centres acheived ADRs for 2012 varying from 60.1% to 32.7% with 26/30 above the QA standard of 35%ADR. We looked in detail at the ADRs of two colonoscopists in Norwich, who acheived ADRs of 60.1% (endoscopist A) and 35.3% (endoscopist B), over a 2 year timespan. Results: Endoscopist A performed 441 colonoscopies and endoscopist B 544. Endoscopist A detected 815 adenomas and endoscopist B 545 (p < 0.0001), with endoscopist A recorded no adenoma or cancer in 125/441 patients vs endoscopist B 251/544 (p < 0.0001). Each endoscopist detected similar numbers of pedunculated adenomas (112/441 vs 130/544) (p = 0.5866) but endoscopist A identified significantly more sessile adenomas 700/441 vs 409/544 (p < 0.0001). Adenomatous polyps were graded by size : > 10 mm A 113/441 vs B 95/544 (p = 0.0018); 6–10 mm A 165/441 vs B 132/544 (p < 0.0001); and < 6 mm A537/441 vs B 318/544 (p < 0.0001). Endoscopist A detected more adenomas proximal to the splenic flexure 425/441 vs B 205/544 (p < 0.0001), whereas the ADRs distal to the splenic flexure were similar A330/441 vs B 340/544 (p < 0.0001). Endoscopist A had a higher completion rate of 99.7% compared with 94.67% for endoscopist B (p < 0.0001). Withdrawal times were similar (for procedures in which no polyps were found) A 10.59 min vs B 9.28 min. Conclusion: Sessile polyps in the right colon are commonly overlooked even by expert bcss accredited colonoscopists. Over half the patients discharged from the programme by endoscopist B with a "normal" colon have had a small right sided adenoma overlooked and it seems likely this is the reason that colonoscopy fails to prevent the development of right sided colonic cancer. The current QA standard for ADR in bcss is too low at 35%. The current JAG QA standard for ADR among the wider colonoscopy community is 10% and it is likely that this problem is widespread. Disclosure of Interest: None Declared. References: Baxter NN, Goldwasser MA, Paszat LF, et al. Association of colonoscopy and death from colorectal cancer: a population-based, casecontrol study. Ann Intern Med 2009; 150 :1–8. Brenner H, Hoffmeister M, Arndt V, et al. Protection from right- and left-sided colorectal neoplasms after colonoscopy: population-based study. J Natl Cancer Inst 2010; 102:89–95.